La enseñanza musical como medio educomunicativo para niños, jóvenes y adultos mediante la realización de una página web que permitirá la difusión del sistema de estudio y los métodos prácticos que propone la Academia de Música Richard Wagner. - Saguay Herrera, Diana Carolina (2012)
The term educational technology involves the design, organization and overall evolution of the learning in the light of theories of learning and communication, making use of human and technical resources, is used to meet the high demand for trained personnel to local education and the large number of students who overcome by educommunication can show that virtual contact between users is done through an electronic platform, where the materials, resources and work plan submitted properly act as means to make progress and develop the activities, assessments and consolidate learning.